2023
DOI: 10.3390/life13030755
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in COVID-19 Patients with Pneumonia Treated with High-Flow Oxygen Therapy and Baricitinib—Retrospective Single-Center Study

Abstract: Background. The aim of the study was to assess the effect of baricitinib on 28-day all-cause mortality and the progression of respiratory failure in patients needing transfer to the intensive care unit (ICU) with COVID-19 pneumonia treated with high-flow oxygen therapy. Methods. This retrospective study included hospitalized patients with COVID-19 pneumonia treated with high-flow oxygen non-invasive ventilation receiving standard of care (SOC) or SOC in addition to baricitinib. Data on patients’ characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…The use of baricitinib was associated with the better survival (HR 0.39, 95% CI 0.21–0.72) in the multivariate COX proportional analysis when adjusted for other covariates. These findings are consistent with the results of the COV-BARRIER study ( 46 ), A retrospective single-center study ( 47 ) comparing outcomes in patients treated with HFNC also reported a significantly lower 28-day all-cause mortality rate in patients treated with baricitinib compared to the standard care group. The vaccinal status is well known as a predictor of outcomes in patients with COVID 19 ( 48–50 ), and in our study, it also emerged as a significant negative predictor of mortality.…”
Section: Discussionsupporting
confidence: 87%
“…The use of baricitinib was associated with the better survival (HR 0.39, 95% CI 0.21–0.72) in the multivariate COX proportional analysis when adjusted for other covariates. These findings are consistent with the results of the COV-BARRIER study ( 46 ), A retrospective single-center study ( 47 ) comparing outcomes in patients treated with HFNC also reported a significantly lower 28-day all-cause mortality rate in patients treated with baricitinib compared to the standard care group. The vaccinal status is well known as a predictor of outcomes in patients with COVID 19 ( 48–50 ), and in our study, it also emerged as a significant negative predictor of mortality.…”
Section: Discussionsupporting
confidence: 87%